Determinants Of Millenial Generations Interest In Using Mobile Banking - Sarmiana Batubara; Ihdi Aini; Yuli Agustina (Institut Agama Islam Negeri Padngsidimpuan, 2021)
Abstract Mobile banking services issued by the banking world, are aimed at making it easier for customers to make transactions that are supported by mobile phones and internet networks. Even so, there are still many customers who have not used mobile banking, especially Islamic mobile banking, including those from the millennial generation who should be more receptive to change and the millennial generation is more technology literate and easy to master technology. In the economic activities of the millennial generation, many transactions are online, starting from shopping on the marketplace, social media and other electronic media. This study aims to determine the factors that influence the interest of the millennial generation in using mobile banking at Islamic banks. This research is a quantitative research. The data source used is primary data. The data collection techniques used were interviews and questionnaires. Respondents in this study were the millennial generation as many as 93 people. The results of this study are that there are several factors that influence the interest of the millennial generation in using Islamic bank mobile banking, namely the factors of convenience, benefits, trust and risk. Based on the results of data analysis that has been carried out, the factors of convenience, benefits, trust and risk have an effect on the interest of the millennial generation in using mobile banking at Islamic banks both partially and simultaneously.